Mapa de España en representación volumétrica de doble constricción población por municipios (1991)(Escala 1:1.250.000) - Calvo Palacios, José Luis; Pueyo Campos, Ángel (Geographicalia, 2017)
Population's map of Spain (1991) in volumetric black and white representation by municipalities. Scale 1:1.250.000. The article is a technical commentary about cartography.
Keywords: Spain; population; cartography